The anti-inflammatory effects and the inhibition of neutrophil responsiveness by Barleria lupulina and Clinacanthus nutans extracts - Wanikiat P. (2014)
Aim of the study: To investigate the anti-inflammatory activities of Barleria lupulina Lindl and Clinacanthus nutans (Burm.f.) Lindau extracts using two neutrophil-dependent acute inflammatory models and, in order to elucidate underlying cellular mechanisms, the effects of the extracts on human neutrophil responsiveness was investigated. Materials and methods: The in vivo inflammatory models examined were carrageenan-induced paw oedema and ethyl phenylpropiolate-induced ear oedema in rats. Myeloperoxidase (MPO) activity was assayed as an indicator of neutrophil migration. Human neutrophil functional responsiveness was determined by measuring fMLP-induced chemotaxis, superoxide anion generation (SAG), and release of MPO and elastase. Apoptosis was assessed morphologically and flow-cytometrically. Neutrophil viability was assessed by trypan blue exclusion and MTT cytotoxicity assays. Results: Both extracts induced powerful dose-dependent inhibitory effects in both edema models in rats. Importantly, there was a significant inhibition of MPO activity in the inflamed tissue indicating that the anti-inflammatory effect of the extracts is associated with reduced neutrophil migration. Although both extracts did not affect neutrophil viability or apoptosis, treatment of neutrophils with the extracts concentration-dependently inhibited fMLP-induced chemotaxis, SAG, and MPO and elastase release. Conclusions: These findings suggest that the powerful anti-inflammatory properties of Barleria lupulina Lindl and Clinacanthus nutans (Burm.f.) Lindau extracts are mediated, in part, by inhibition of neutrophil responsiveness.Barleria lupulina Lindl, Clinacanthus nutans (Burm. f.)Lindau; Oedema formation; Neutrophil responsiveness. © 2007 Elsevier Ireland Ltd. All rights reserved.